2012
DOI: 10.1097/rct.0b013e318256b1e2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dual Vascular Input Functions on CT Perfusion Parameter Values and Reproducibility in Liver Tumors and Normal Liver

Abstract: Objective To assess the impact on absolute values and reproducibility of adding portal venous (PV) to arterial input functions in computed tomography perfusion (CTp) evaluations of liver tumors and normal liver. Methods Institutional review board approval and written informed consent were obtained; the study complied with HIPAA regulations. CTp source datasets, obtained from seven patients (containing 9 liver tumors) on two occasions, 2-7 days apart, were analyzed by deconvolution modeling using dual (“Liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The perfusion values of the metastases and the normal surrounding liver parenchyma were significantly different. These findings are similar to the results of other studies that included patients with other cancers, such as liver metastases from neuroendocrine tumours [25,26].…”
Section: Discussionsupporting
confidence: 90%
“…The perfusion values of the metastases and the normal surrounding liver parenchyma were significantly different. These findings are similar to the results of other studies that included patients with other cancers, such as liver metastases from neuroendocrine tumours [25,26].…”
Section: Discussionsupporting
confidence: 90%
“…Double baseline DCE-CT scans indicated an average reproducibility of 5%, which is an order of magnitude better than perfusion variability reported previously using DCE scans 1 week apart on a 16-slice CT scanner, 25 as well as from DCE-MRI measurements 26 . This is likely also a conservative estimate given the unplanned pressure shutoff of 1 of the scans.…”
Section: Discussionmentioning
confidence: 57%
“…However, this assumption may not hold true for all histologic types of metastases as some liver metastases may have a mixed vascular supply (42,43). Ng et al (44) recently reported that a dual vascular input model (arterial and portal venous) for analysis of CT perfusion data sets improves test-retest reproducibility. Indeed, the separation of Plot of time-intensity curve of spleen and liver from CT perfusion study using maximum slope method.…”
Section: Single-compartment Versus Dual-compartment Modelmentioning
confidence: 99%
“…Therefore, most CT perfusion studies of the liver have used a dual-compartment model to better reflect the microcirculation of the diseased liver resulting from tumor or cirrhosis, although dual-compartment models are computationally more demanding (43). hepatic arterial and portal venous blood supply in normal liver tissue and liver lesions is important for characterization and treatment response evaluation of liver nodules (44)(45)(46). For instance, when hepatocellular dysplastic nodules evolve to HCC, the intranodular portal supply decreases while the intranodular arterial supply increases in parallel with formation of unpaired arteries.…”
Section: Calculation Of Ct Perfusion Parametersmentioning
confidence: 99%